2014
DOI: 10.1007/s11999-014-3538-5
|View full text |Cite
|
Sign up to set email alerts
|

Biofilm Growth Has a Threshold Response to Glucose in Vitro

Abstract: Postoperative hyperglycemia may increase the risk for implant infection through increased pathogenicity of intraoperative wound contaminants in addition to compromising host immune status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
37
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(48 citation statements)
references
References 19 publications
5
37
0
Order By: Relevance
“…However, in this situation water became a limiting factor due to the high sugar concentration in the surrounding media. These data are similar to previous findings of a number of researchers [23][24][25]. Both sugars are known to promote the production of a floccular, fibrillar layer, especially in C. albicans, which is thought to mediate adhesion and subsequent biofilm formation [26].…”
Section: Discussionsupporting
confidence: 91%
“…However, in this situation water became a limiting factor due to the high sugar concentration in the surrounding media. These data are similar to previous findings of a number of researchers [23][24][25]. Both sugars are known to promote the production of a floccular, fibrillar layer, especially in C. albicans, which is thought to mediate adhesion and subsequent biofilm formation [26].…”
Section: Discussionsupporting
confidence: 91%
“…Significance symbols for the qRT-PCR data of expression of genes in bile salts compared to the expression of genes in media without bile salts: ***, P Ͻ 0.0001; *, P Ͻ 0.05; n.s., not significant. biofilm formation, particularly for EPS production, has been documented for many pathogens, including Vibrio (51, 52), Listeria (53), Pseudomonas (54), Acinetobacter (55), and Staphylococcus (56). To further highlight the importance of glucose in biofilm formation, the RNA-seq analysis demonstrated that the ptsG gene, encoding the glucose-specific phosphoenolpyruvate phosphotransfer system (PTS) IIBC components, was induced in S. flexneri 2457T in the presence of bile salts as seen with Vibrio biofilms (51, 52).…”
Section: Figmentioning
confidence: 99%
“…Even glucose concentrations may impact biofi lm formation, potentially infl uencing infections in patients with diabetes mellitus. For example, it has recently been demonstrated that biofi lm biomass was increased at higher glucose concentrations for both S. epidermidis and S. aureus with a threshold response at 0-20 and 160-200 mg/dL for S. epidermidis and 200-240 mg/dL for S. aureus (Waldrop et al 2014 ).…”
Section: Infl Uence Of Host Factors On Biofi Lm Formationmentioning
confidence: 99%